Kajian Nutrisi dan Budi Daya Maggot (Hermentia illuciens L.) Sebagai Alternatif Pakan Ikan di RT 02 Desa Purwasari, Kecamatan Dramaga, Kabupaten Bogor - Amira Amandanisa; Prayoga Suryadarma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
The problem in Purwasari Village is the large amount of organic waste that is produced by household and agricultural industries that have not been properly managed, causing unpleasant odors. The waste is in the form of pieces of vegetables, fruit skins and meat bones. In addition, in the fisheries sector, fish farmers who still use pelets as fish feed, given the rising price of pelets, farmers must find other alternatives to reduce feed costs, one of the solutions is maggot cultivation as a substitute for animal feed which has a high protein content. SUIJI SLP held a socialization activity for maggot cultivation as an alternative to animal feed which was carried out in Purwasari Village. The method implemented is lecture, discussion and practice. Prior to the socialization, surveys and field observations and literary methods were carried out. Information from interviews was strengthened by conducting a literature review relevant to the topic. The result of this socialization was the enthusiasm of the community was evidenced by an interactive discussion between the lecturer and the community. Keywords: Alternative animal feed, black soldier fly, organic waste, magot.